2015
DOI: 10.1515/ehs-2014-0009
|View full text |Cite
|
Sign up to set email alerts
|

Floor Tile Energy Harvester for Self-Powered Wireless Occupancy Sensing

Abstract: We investigate a concept that can reduce the overall power requirement of a smart building through improvements in the real-time control of HVAC and indoor lighting based on the building occupancy. The increased number of embedded sensors necessary to realize the smart building concept results in a complex wiring and power structure. We demonstrate a floor tile energy harvester for creating a wireless and self-powered occupancy sensor. This sensor termed as "Smart Tile Energy Production Technology (STEP Tech)"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 23 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…If it is used a large number of transducers, the more potential there is for energy to be harvested before the transducers become overloaded, but it decreases the sensitivity of the tile, or the amount of energy produced per load. Therefore, it is an optimum number of transducers to be employed for maximum energy harvesting from a target weight [4]. Sharpes et al [4] have found that for a child (32 kg) the optimum number of transducers is 4, for an average adult (82 kg) is 8 transducers and for a 115 kg adult, the optimum number is 14 transducers.…”
Section: Optimizationmentioning
confidence: 99%
See 3 more Smart Citations
“…If it is used a large number of transducers, the more potential there is for energy to be harvested before the transducers become overloaded, but it decreases the sensitivity of the tile, or the amount of energy produced per load. Therefore, it is an optimum number of transducers to be employed for maximum energy harvesting from a target weight [4]. Sharpes et al [4] have found that for a child (32 kg) the optimum number of transducers is 4, for an average adult (82 kg) is 8 transducers and for a 115 kg adult, the optimum number is 14 transducers.…”
Section: Optimizationmentioning
confidence: 99%
“…Therefore, it is an optimum number of transducers to be employed for maximum energy harvesting from a target weight [4]. Sharpes et al [4] have found that for a child (32 kg) the optimum number of transducers is 4, for an average adult (82 kg) is 8 transducers and for a 115 kg adult, the optimum number is 14 transducers. However, a tile optimized for a child can make more energy per step at low weights, but has a much lower maximum possible energy production compared to a tile optimized for an adult [4].…”
Section: Optimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Investigations on energy‐harvesting floors have been conducted by researchers from academia and companies. Sharpes designed a tile based on PZT cymbal transducers capable of powering wireless signal transmissions, and Bischur proposed using PVDF‐based modules . Notable efforts have been conducted in developing electromagnetic energy‐harvesting tiles .…”
Section: Introductionmentioning
confidence: 99%